2017
DOI: 10.1038/srep40388
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome profiling-guided depletion of an mRNA increases cell growth rate and protein secretion

Abstract: Recombinant protein production coopts the host cell machinery to provide high protein yields of industrial enzymes or biotherapeutics. However, since protein translation is energetically expensive and tightly controlled, it is unclear if highly expressed recombinant genes are translated as efficiently as host genes. Furthermore, it is unclear how the high expression impacts global translation. Here, we present the first genome-wide view of protein translation in an IgG-producing CHO cell line, measured with ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…Treatment of siRNA depleted NeoR mRNA 87-92% resulting in an increase in both VCD and titer. 13 Fomina-Yadlin also showed strong correlation between mRNA levels and qP for a recombinant Fc-fusion protein and up to 45% of total cellular mRNA levels encoded the recombinant transcript for cultures treated with chemicals that induce gene expression. 24 We did not observe substantial differences in growth during production phase between pools selected while constitutively expressing recombinant protein compared to those only expressing recombinant protein during production phase (Figure 5b and Figure S3b).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Treatment of siRNA depleted NeoR mRNA 87-92% resulting in an increase in both VCD and titer. 13 Fomina-Yadlin also showed strong correlation between mRNA levels and qP for a recombinant Fc-fusion protein and up to 45% of total cellular mRNA levels encoded the recombinant transcript for cultures treated with chemicals that induce gene expression. 24 We did not observe substantial differences in growth during production phase between pools selected while constitutively expressing recombinant protein compared to those only expressing recombinant protein during production phase (Figure 5b and Figure S3b).…”
Section: Discussionmentioning
confidence: 92%
“…In that example, the NeoR mRNA accounted for 5.63% of translated mRNAs on Day 3 and 5.41% on Day 6. Treatment of siRNA depleted NeoR mRNA 87–92% resulting in an increase in both VCD and titer . Fomina‐Yadlin also showed strong correlation between mRNA levels and qP for a recombinant Fc‐fusion protein and up to 45% of total cellular mRNA levels encoded the recombinant transcript for cultures treated with chemicals that induce gene expression …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…On-the-other-hand, feeding of cells resulted in an increase in global translational activity and an increase in specific heavy and light chain translation [25]. The third found that recombinant mRNAs are translated as efficiently as host cell transcripts and occupied up to 15% of total ribosome capacity [26]. Collectively these studies conclude that a better understanding of global and target specific translational efficiency and reprogramming in CHO cells could aid in the development of feeding strategies to prolong growth and recombinant protein production and identify targets for cell engineering strategies to prolong or enhance recombinant gene synthesis.…”
Section: Introductionmentioning
confidence: 98%